VALIDITAS DAN RELIABILITAS INSTRUMEN “3-MINUTE NUTRITIONAL SCREENING (3-MinNS)" UNTUK MENGKAJI RISIKO MALNUTRISI PADA PASIEN HIV DAN AIDS - Maria Syelvrida Tumina; Agung Waluyo; Sri Yona (JURNAL KEPERAWATAN, 2023)
Background: Nutrition and HIV are problems that need serious more attention because they will accelerate the weakening of the body’s immune system and the expansion of opportunistic infections. HIV infection is known to cause significant nutritional problems in the infected population, so a screening instrument is needed to identify malnutrition problems in patients with HIV. A comprehensive assessment of nutritional status will help deciding the next intervention. One of the malnutrition screening instruments that has been tested is the 3-Minute Nutrition Screening Tool which highly sensitive and specific. Objective: The aim of this article is to determine the validity and reliability of the 3-MinNS tool in assessing the risk of malnutrition in patients HIV/AIDS. Method: The quantitative method was used in this study and the data was analyzed with SPSS version 16. The sample in this study was 30 respondents with the inclusion criteria as follow: HIV/AIDS patient, aged over 18 years and not pregnant. Results: The results of the analysis show that all items in the 3-MinNS tool instrument were valid with a value of 0.794-0.798 and a cronbach alpha value of 0.889 Most of the respondents had severe malnutrition (70%) and had low CD4 counts (66,7%). Conclusion: These result indicate that the 3-MinNS tool is valid and reliable for assessing the risk of malnutrition in patients with HIV/AIDS. Hence,3-MinNS tool is highly recommended for malnutrition screening in patients with HIV.AIDS patients in hospitals. Keywords: HIV/AIDS; malnutrition; 3-Minute Nutrition Screening Tool